Influence of ion implantation on the near-surface structure of thin Ni and Pd films on lithium niobate and lithium tantalate - Lysiuk, V.O.; Staschuk, V.S.; Kluy, M.I.; Vakulenko, O.V.; Poperenko, L.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2007)
The systems “thin Ni film – lithium niobate” and “thin Pd film – lithium tantalate” are implanted by Ar⁺ ions with an energy of 100 keV and a dose of 10¹⁶ cm⁻². Analyses of the systems by AFM and SEM have shown that the ion implantation essentially modifies the near-surface structure resulting in a change of its optical, electrical, and mechanical properties. Strong difference in the near-surface structures between implanted systems with Ni or Pd thin films is observed. Such a difference is explained by the heterogeneity of an ion beam and different properties of the materials. The application to the development of high-sensitive pyroelectric detectors with high damage threshold is proposed.